The Influence of Principal Leadership Style and Organizational Culture on Teacher Performance with Job Satisfaction as a Factor Mediating Variables In Elementary Schools - Rasidi, Anang; Sembiring, M. Gorky; Rosita, Tita (Elementary Teacher Education Program, Majalengka University, 2025)
This study aimed to analyze the influence of principal leadership style and organizational culture on teacher performance with job satisfaction as a mediating variable in elementary schools in Obaa District of Mappi Regency. The background of this study is the low Human Development Index (HDI) Papua which reflects the low quality of education and teacher performance is not optimal. This study uses a quantitative approach with path analysis techniques and involves 100 teachers as respondents selected through purposive sampling. The results showed that the principal's leadership style and organizational culture have a significant effect on Teacher Job Satisfaction, and job satisfaction has a significant effect on teacher performance. In addition, job satisfaction was shown to significantly mediate the relationship between principal leadership style and organizational culture on teacher performance. The conclusion of this study is that improved teacher performance is strongly influenced by effective leadership and positive organizational culture through increased job satisfaction. It is recommended that school principals adopt a participatory leadership style and build a conducive organizational culture to improve job satisfaction and teacher performance on an ongoing basis.